Bevacizumab plus low-dose metronomic oral cyclophosphamide in heavily pretreated patients with recurrent ovarian cancer - Sánchez-Muñoz, Alfonso; Mendiola, César; Pérez-Ruiz, Elisabeth; Rodríguez-Sánchez, César A.; Jurado, José Miguel; Alonso-Carrión, Lorenzo Javier; Ghanem, Ismael; Velasco, Guillermo de; Quero-Blanco, Cristina; Alba-Conejo, Emilio (KARGER, 2010)
Aim: To retrospectively assess the efficacy and safety of bevacizumab plus low-dose metronomic oral cyclophosphamide in heavily pretreated patients with recurrent ovarian cancer. Patients and Methods: Patients with recurrent ovarian cancer and prior treatment with platinum- and taxanebased chemotherapy were included. Treatment consisted of bevacizumab 10 mg/kg intravenously every 2 weeks plus oral cyclophosphamide 50 mg daily until disease progression or unacceptable toxicity. Response rates (RR) were determined according to RECIST criteria and by monitoring the CA 125 serum tumor marker according to Rustin’s criteria.The endpoints were progression-free survival (PFS), RR, overall survival (OS), and safety. Results: Thirty-eight patients were treated; 79% were platinum resistant and 21% were platinum sensitive. The median number of previous treatments was 4 (range 1–8). Seventy-nine percent of patients had received more than 2 previous lines of treatment. Eightyone percent of patients had received gemcitabine, 76% liposomal doxorubicin, and 50% topotecan. A median of 8 (range 1–70) cycles of bevacizumab were administered. The overall RR was a complete response (CR) in 3 patients (8.1%), a partial response (PR) in 12 (32.4%), and stable disease (SD) 6 6 months in 3 (8.1%). The median PFS and OS were 4.5 and 10.7 months, respectively. Thirty-nine percent of patients were progression free for at least 6 months. In an exploratory analysis there was a significant relation of prior platinum response and performance status with the risk of progression.Grade 3–4 toxicities included anemia (1), hypertension (2), hematuria (1), arterial thrombosis in the leg (1), dyspnea (1), and intestinal fistulae (1). There were no cases of gastrointestinal perforation (GIP) or treatment-related deaths. Conclusion: The combination of bevacizumab and metronomic cyclophosphamide was active and well-tolerated in heavily pretreated patients with recurrent ovarian cancer.
Este artículo ha sido publicado en Oncology Basel. Esta versión tiene Licencia Creative Commons CC-BY-NC-ND No puedo enviar el postprint porque no lo tienen disponible o no quieren facilitarmelo, en su lugar he aportado en la descripción del envió dos e mail en los cuales la editorial me da permiso por escrito para su depósito como puede ver en los mimos Adjunto e mails, si tiene ustd alguna otra sugerencia para poder hacer deposito por favor hagamelo saber 2º e mail: Dear Alfonso, Our reply is the written permission to deposit the article in the university’s repository – please find it attached once again. Kind regards, Veronika 1º e mail Veronika Duhovnikova Key Account Manager, Academic & Research Markets +41 61 306 12 43 v.duhovnikova@karger.com Dear Alfonso, Thank you for your email. As to your query, we are pleased to inform you that Karger permits authors to archive their pre-prints (i.e. pre-peer review) or post-prints (i.e. accepted manuscript after peer review but before production) on their personal or their institution’s internal website. In addition, authors may post their accepted manuscripts in public Open Access repositories and scientific networks (e.g. ResearchGate or Mendeley) no earlier than 12 months following the publication of the publisher’s versions. For all self-archiving options, the posted manuscripts must be - used for non-commercial purposes only - linked to the final version on Karger Publishers - include the following statement: ‘This is the peer-reviewed but unedited manuscript version of the following article: [insert full citation, e.g. Oncology 1 December 2010; 79 (1-2): 98–104, (DOI: 10.1159/000320602)]. The final, published version is available at [https://karger.com/ocl/article-abstract/79/1-2/98/328844/Bevacizumab-plus-Low-Dose-Metronomic-Oral?redirectedFrom=fulltext].’ For papers published online first with a DOI number only, full citation details must be added as soon as the paper is published in its final version. This is important to ensure that citations can be credited to the article. It is the author’s responsibility to fulfil these requirements. Further information about Karger’s Self-Archiving Policy can be found on the Karger website https://karger.com/pages/rights-and-permissions ‘How can I share it?’ and on SherpaRomeo Welcome to Sherpa Romeo - v2.sherpa. Please feel free to contact us again, if you need any further information. Kind regards, Veronika Veronika Duhovnikova Key Account Manager, Academic & Research Markets +41 61 306 12 43 v.duhovnikova@karger.com
Keywords: Ovarios - Cáncer - Tratamiento; Bevacizumab; Cyclophosphamide; Recurrent ovarian cancer